The Relationship of Students‘ Learning Motivation and Their Speaking Performance - Alfiana, Evelyne Sari; Wijirahayu, Suciana (Scripta : English Department Journal, 2024)
A skill to consider when learning English is speaking. Students need confidence in their English ability and to feel capable when speaking to others their age. In this situation, it is also essential for students to acquire simple language, and give them the confidence to communicate well. This study investigated the relationship between students’ learning motivation and speaking performance students‘. The students in grade 12 in a vocational high school in East Jakarta will be the participants. A questionnaire is an instrument used to measure learning motivation. This study shows how vital learning motivation is for students and how it affects their ability to speak English well. The researcher collected and analyzed data using a questionnaire. The study’s findings indicate that learning motivation improves students’ speaking abilities. This can also be determined by students’ speaking scores, which have met the Maximum Completion Criteria (MCC). The average score of students in this speaking lesson is 7.5, and the average score of students’ motivation is 3.9 out of 5. This means that students remain motivated to learn to speak. In addition, students’ motivation for speaking education has increased significantly. The above explanation explains that there is a positive correlation between the motivation of students and the ability to communicate.